PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE PAIR CHECK BERBANTUAN WORDWALL TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV UPTD SD NEGERI 62 PAREPARE - Desi; Muhammad Asrul Sultan; Zaid Zainal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the cooperative learning model type Pair Check assisted by Wordwall on the mathematics learning outcomes of fourth grade students at UPTD SD Negeri 62 Parepare. The research used a quantitative approach with a quasi-experimental method in the form of a nonequivalent control group design. The population consisted of all students at UPTD SD Negeri 62 Parepare, with the sample being class IV.A as the experimental class, consisting of 26 students, and class IV.B as the control class, consisting of 24 students. Data were collected through a multiple-choice test consisting of 20 questions. The data analysis technique used was inferential statistical analysis with an independent sample t-test. The data analysis technique used was an independent sample t-test. The results of the inferential statistical analysis using the independent sample t-test showed Sig (2-tailed) = 0.000≤0.05, indicating that H0 was rejected and H1 was accepted. Thus, the conclusion of this study is that there is an effect of the cooperative learning model of the pair check type assisted by Wordwall on the mathematics learning outcomes in the topic of area and perimeter of plane figures for fourth-grade students at UPTD SD Negeri 62 Parepare.